Philosophy of Education in Madrasah Ibtidaiyah: Ontological, Epistemological, and Axiological Analysis and Practical Implications for Teachers - Umi Salamah; De Gigin Herdiana; Sofi Mutiatuzzahra; Tamsik Udin (Penerbit Hellow Pustaka, 2026)
Madrasah Ibtidaiyah plays a strategic role in shaping students’ basic personality, faith, and intellectual development. Educational philosophy functions as a conceptual foundation that determines the direction, objectives, and practices of Islamic education at the elementary level. This article aims to examine the philosophy of education in Madrasah Ibtidaiyah through ontological, epistemological, and axiological perspectives, as well as to analyze its practical implications for Madrasah Ibtidaiyah teachers. This study employs a qualitative literature review approach based on classical and contemporary Islamic educational philosophy sources. The findings reveal that Islamic educational philosophy provides a holistic framework for curriculum development, instructional methods, and Islamic character building. Practically, it requires Madrasah Ibtidaiyah teachers to act not only as instructors but also as moral guides and role models of Islamic values.